Measurement of the muon-induced neutron flux at LNGS with the LVD experiment - Persiani, Rino <1980> (Alma Mater Studiorum - Università di Bologna, 2011)
In this thesis we describe in detail the Monte Carlo simulation (LVDG4) built to interpret the experimental data collected by LVD and to measure the muon-induced neutron yield in iron and liquid scintillator. A full Monte Carlo simulation, based on the Geant4 (v 9.3) toolkit, has been developed and validation tests have been performed.